Fuzzy Adaptive Event-Triggered Secure Control for Stochastic Nonlinear High-Order MASs Subject to DoS Attacks and Actuator Faults - Shao, Xinfeng; Ye, Dan (IEEE transactions on fuzzy systems, 2021)
This article investigates the adaptive event-triggered secure control design problem for a class of stochastic nonlinear high-order multiagent systems (MASs) subject to denial-of-service (DoS) attacks and actuator faults. The considered systems contain not only unknown random interference terms but also general nonlinear functions that are not required to be globally Lipschitz, in contrast to most of the existing results in the area. To solve the problem of wasted communication resources, the control signal with the relative threshold strategy is designed via the event-triggered control technique. As a class of cyber-physical systems, the securities of MASs are vulnerable to actuator faults and DoS attacks. When the system suffers from coupled DoS attacks and actuator failures, its performance will deteriorate rapidly and even the controlled system will collapse. To overcome this difficulty, a novel fault-tolerant and antiattack control method is proposed, which enables the system to achieve the security control objective even in an insecure network and physical environment. The stability analysis of the system is given by combining the adaptive backstepping recursive design process with stochastic Lyapunov stability theory. It is demonstrated that all the signals of the closed-loop systems are semiglobally uniformly ultimately bounded in probability. Finally, a simulation example is given to illustrate the effectiveness and advantages of the presented scheme.